17. yüzyılda yapılmış mensur Şehname tercümesi 160a-200b - Algan, İshak (My University, 2005)
Eser, İstanbul Üniversitesi Merkez Kütüphanesi 6131 demirbaş numarasıyla kayıtlıdır. Üç cilt halinde ve tamamı 1778 varaktır. Ayrıca eserde minyatürlere yer verilmiş, her sayfası 25 satır olarak düzenlenmiştir. Üzerinde çalışılan 1. cildin boyu 39, eni 24.5, kalınlığı 7.5 cm'dir. Eser Hicrî 1187, milâdî 1773 yılında tamamlanmıştır, kelime kelime bir tercüme değildir. Tez yazmanın 160a-200b varaklarını kapsamaktadır. Eserin 01b - 40b varakları Sadettin ŞAHİN, 41a-80b varakları ise Sema DEMİREL ŞAHİN tarafından olarak hazırlanmıştır. Bu tezi hazırlamaktaki amaç Şehnâme'nin bu mensur tercümesini tanıtmaktır. Bu çalışma giriş, metin ve sözlük olmak üzere üç bölümden oluşmaktadır. Giriş kısmında Firdevsî, Şehname, Şehname çevirileri ve üzerinde çalışılan yazmayla ilgili bilgiler verilmektedir. Ayrıca aradaki farklılıkları ve benzerlikleri göstermesi, bir fikir vermesi açısından Şehnâme çevirilerindeki bazı kişi, olay ve durumlar Necati Lugal'in Farsça'dan yaptığı birebir tercüme, Şerîfî Şehnâme Çevirisi ve 17. Yüzyılda Yapılmış Mensur Şehnâme Tercümesi (160a-200b varakları arası) esas alınarak karşılaştırılmıştır. Metin kısmında sayfa ve satır numaraları belirtilmiş, günümüz noktalama işaretlerine göre düzenlenmiş ve gerekli kısımlarda paragraflar yapılmıştır. Böylece eserden faydalanılması daha kolay hale getirilmek istenmiştir. Sözlük bölümünde eserin söz varlığını gösteren bir indeks hazırlanmış; eserdeki kelime ve birleşik şekillerin metindeki anlamları verilmeye çalışılmıştır.

The book is registered under fixture number 6131 at the Central Library of Istanbul University. It is composed of 3 volumes with total pages of 1778. Also miniatures have taken place in the book with each page designed in 25 lines. The length of the first volume on which the work is being carried on, is 39 cm, the width is 24.5 cm and thickness is based 7.5 cm. The work was completed in 1187 - date based on Hegira, in 1773 - date based on Christian Era; it is not a translation word by word. The thesis includes the pages 160a - 200b of the manuscript. The pages 01b - 40b have been prepared by Sadettin ŞAHİN, and pages 41a - 80b have been prepared by Sema ŞAHİN as a master's thesis. The aim in preparing this thesis is to introduce the translation of Şehnâme as a prose. This work is composed of three sections which are the introduction, the text and the dictionary. In the introduction part, information about Firdevsî, Şehnâme, Şehnâme translations and the manuscript on wich the work is carried on; is given. Also, to show the differences and similarities, and give an opinion; same people, events and situations in Şehnâme translations are compared, based on the translation from Persian made by Necati Lugal, Şerîfî Şehnâme Translation and Prose Şehnâme Translation ( between the pages of 160a - 200b) In the text, the page and line numbers are shown, designed according to today's punctuation marks and in necessary parts paragraphs are created. In this way, it has been aimed to get benefit of the work more easily. In dictionary, an index is prepared which shows the vocabulary of the book; the meanings of the words and compound forms in the book are tried to be explained.
Keywords: Edebiyat; İran edebiyatı; İran Edebiyatı_Şehname